ANALISIS BIBLIOMETRIK: PENGARUH PROGRESSIVE MUSCLE RELAXATION TERHADAP KECEMASAN PADA ATLET - Muhammad Imaduddin; Sali Rahadi Asih (Universitas Hamzanwadi, 2026)
Competitive anxiety is a major psychological challenge that affects athletes' performance, but comprehensive mapping of Progressive Muscle Relaxation (PMR) research in this context is still limited. This study aims to analyze and map the development of scientific publications related to the effect of PMR on anxiety in athletes through a bibliometric approach. Data were obtained from the Scopus database using the keywords “progressive muscle relaxation,” “anxiety,” and “athlete*” in the range of 2004–2024. A total of 82 articles that met the inclusion criteria were analyzed using VOSviewer and Bibliometrix-RStudio to map annual productivity, citation patterns, productive journals, keyword co-occurrence, and thematic mapping. The results showed fluctuations in the number of publications with a significant increase after 2019 and a peak in 2021. Frontiers in Psychology and Psychology of Sport and Exercise are the most productive journals. Keyword analysis reveals the dominance of themes such as mindfulness, mental health, stress regulation, and athletic performance. Thematic mapping identifies motor themes such as psychophysiology of heart rate that have potential for further development. The conclusions of this study confirm that PMR contributes significantly to reducing athletes' anxiety and is integrated into a broader psychological approach. Further research is recommended to explore the effectiveness of PMR experimentally across sports and cultural contexts.